2020
DOI: 10.3390/nano10091785
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir-Loaded Solid Lipid Nanoparticles: Optimization, Characterization and Evaluation of Its Pharmacokinetic Profile

Abstract: Acyclovir is an antiviral drug used for the treatment of herpes simplex virus infection. Its oral bioavailability is low; therefore, frequent and high doses are prescribed for optimum therapeutic efficacy. Moreover, the current therapeutic regimen of acyclovir is associated with unwarranted adverse effects, hence prompting the need for a suitable drug carrier to overcome these limitations. This study aimed to develop solid lipid nanoparticles (SLNs) as acyclovir carriers and evaluate their in vivo pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…The intermediate positive charge observed for this pilot scale formulation, +9.8 mV, is postulated to be due to the presence of the Tween 80 layer. Similar effects have been observed by Hassan et al, where Tween 80 was shown to produce a “less negative” surface charge for solid lipid nanoparticles [ 59 ]. Lason et al also highlight the transition to a positive charge when using Tween 80 alone as a surfactant for NLC formulation, recording an increase to +17.9 mV from a negative −50.1 mV when used with PlantaCare [ 17 ].…”
Section: Resultssupporting
confidence: 83%
“…The intermediate positive charge observed for this pilot scale formulation, +9.8 mV, is postulated to be due to the presence of the Tween 80 layer. Similar effects have been observed by Hassan et al, where Tween 80 was shown to produce a “less negative” surface charge for solid lipid nanoparticles [ 59 ]. Lason et al also highlight the transition to a positive charge when using Tween 80 alone as a surfactant for NLC formulation, recording an increase to +17.9 mV from a negative −50.1 mV when used with PlantaCare [ 17 ].…”
Section: Resultssupporting
confidence: 83%
“…These findings could be attributed to the full coverage of the non-ionic surfactant, Tween 80, which causes steric hindrance, as well as electrostatic repulsion from the solid lipid [43]. Surprisingly, this was not the case for SLN that was developed using Biogapress Vegetal 297 ATO as solid lipid material, in our previous study [8]. Although the same methods and optimization processes were employed to develop this nanocarrier system, after the first month of storage, the size of the blank Biogapress Vegetal 297 ATO SLN and acyclovir-loaded Biogapress Vegetal 297 ATO SLN formulations stored at room temperature started to increase significantly, and high polydispersity index values were recorded.…”
Section: Discussionmentioning
confidence: 85%
“…In the past, various pharmaceutical formulations, such as lipid-based nanoparticles [ 8 ], polymeric nanoparticulate systems [ 9 ], mixed micelles and niosomal carriers [ 10 , 11 ] have been studied as strategies to increase the solubility and bioavailability of poorly soluble drugs. Several attempts have also been made to incorporate acyclovir into different types of delivery systems, including microemulsion [ 12 ], liposome [ 13 ] and nanoemulsion [ 14 ] to enhance its bioavailability [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 The uptake of SLNs into lymphatic system can occur via two mechanisms: M-cell-mediated uptake and paracellular/transcellular route. 18 Basically, SLN properties such as particle size and shape can affect their bioavailability. Small particles tend to adhere to cell-surface while large particles (>200 nm) are filtered out by reticular meshwork.…”
Section: Biodistributionmentioning
confidence: 99%